Immature stages of the genus Casignetus MacLeay, 1819 (Coleoptera: Lucanidae: Lucaninae) - Silva, Alessandra C.g.; Grossi, Paschoal C. (Zootaxa, 2019)
The immature stages of Casignetus MacLeay, 1819 (Coleoptera: Lucanidae: Lucaninae: Casignetini) are revised with the description of third instars of males and female of C. humboldti (Gyllenhal, 1817), and C. spixi (Perty, 1830), and female of C. lindei (Boileau, 1899). Pupae of both sexes of C. humboldti, and female of C. lindei are also described for the first time. Casignetus larvae can be recognized by the form of the pars stridens, formed by a slightly arched, longitudinal row of robust, and sclerotized teeth, and by the fusion of the femur and trochanter in prothoracic and mesothoracic legs. Additionally, new characters are proposed for Casignetus species: frontal sutures curvature; epicranial setae; epipharynx and hypopharynx setae; and number and shape of stridulatory teeth.